(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Heat of interaction and transfer of alanine, phenylalanine, serine and aspartic acid from water to aqueous surfactant solutions have been determined at 298,15 K. It is shown that the negative values of heat of transfer are the result of interaction of amino acids with hydrophobic chains of surfactants. The process of aminoacids dehydration also has its certain contribution.